Neoarchean Mantle-derived Magmatism within the Repulse Bay Block, Melville Peninsula, Nunavut: Implications for Archean Crustal Extraction and Cratonization - LaFlamme, Crystal; McFarlane, Christopher R.M.; Corrigan, David (Geoscience Canada, 2015)
SUMMARY The Repulse Bay block (RBb) of the southern Melville Peninsula, Nunavut, lies within the Rae craton and exposes a large (50,000 km2) area of middle to lower crust. The block is composed of ca. 2.86 Ga and 2.73–2.71 Ga tonalite-trondhjemite-granodiorite (TTG) and granitic gneiss that was derived from an older 3.25 and 3.10 Ga crustal substrate. This period of crustal generation was followed by the emplacement of ca. 2.69–2.66 Ga enderbite, charnockite, and granitoid intrusions with entrained websterite xenoliths. These voluminous batholith-scale bodies (dehydrated and hydrated intrusions), and the associated websterite xenoliths, have similar whole rock geochemical properties, including fractionated light rare earth element (LREE)–heavy (H)REE whole rock patterns and negative Nb, Ti, and Ta anomalies. Dehydrated intrusions and websterite xenoliths also contain similar mineralogy (two pyroxene, biotite, interstitial amphibole) and similar pyroxene trace element compositions. Based on geochemical and mineralogical properties, the two lithologies are interpreted to be related by fractional crystallization, and to be the product of a magmatic cumulate processes. Reworking of the crust in a ca. 2.72 Ga subduction zone setting was followed by ca. 2.69 Ga upwelling of the asthenospheric mantle and the intrusion of massif-type granitoid plutons. Based on a dramatic increase in FeO, Zr, Hf, and LREE content of the most evolved granitoid components from the 2.69–2.66 Ga cumulate intrusion, we propose that those granitoid plutons were in part derived from a metasomatized mantle source enriched by fluids from the subducting oceanic slab that underwent further hybridization (via assimilation) with the crust. Large-scale, mantle-derived Neoarchean sanukitoid-type magmatism played a role in the development of a depleted lower crust and residual sub-continental lithospheric mantle, a crucial element in the preservation of the RBb. RÉSUMÉ Le bloc de Repulse Bay (RBb) dans le sud de la péninsule de Melville, au Nunavut, est situé dans le craton de Rae et expose une large zone (50 000 km2) de croûte moyenne à inférieur. Ce bloc est composé de tonalite-trondhjémite-granodiorite (TTG) daté à ca. 2,86 Ga et 2,73–2,71 Ga, et de gneiss granitique dérivé d’un substrat crustal plus ancien daté à 3,25 Ga et 3,10 Ga. Cette période de croissance crustale a été suivie par la mise en place entre ca. 2,69 et 2,66 Ga d’intrusions d’enderbite, charnockite et de granitoïde incluant des xénolites d’entraînement de websterite. Ces intrusions de taille batholitique (intrusions déshydratées et hydratées) ainsi que les xénolites d’entraînement de websterite associés, ont des propriétés géochimiques sur roche totale semblables notamment leurs profils de fractionnement des terres rares légers (LREE) et des terres rares lourds (HREE) ainsi que leurs anomalies négatives en Nb, Ti et Ta. Les intrusions déshydratées et les xénolites de websterite ont aussi des minéralogies similaires (deux pyroxènes, biotite, amphibole interstitielle) ainsi que des compositions semblables en éléments traces de leurs pyroxènes. Étant donné leurs propriétés géochimiques et minéralogiques, ces deux lithologies sont interprétées comme provenant d’une cristallisation fractionnée, et comme étant le produit de processus d’accumulations magmatiques. Le remaniement de la croûte dans un contexte de subduction vers ca. 2,72 Ga, a été suivi vers ca. 2,69 Ga d’une remontée du manteau asthénosphérique et de l’intrusion de granitoïdes de type massif. D’après l’importante augmentation en FeO, Zr, Hf et LREE dans les granitoïdes les plus évolués du magmatisme ayant pris place entre ca. 2,69 Ga et 2,66 Ga, nous proposons que ces plutons aient été en partie dérivés d’une source mantélique métasomatisée enrichies par des fluides d’une plaque océanique en subduction et qui a subi une hybridation supplémentaire (par assimilation) avec la croûte. Le magmatisme néo-archéen de type sanukitoïde, dérivé du manteau et de grande échelle, a joué un rôle dans le développement d’une croûte inférieure et d’un manteau lithosphérique continental résiduel appauvri, un élément déterminant pour la préservation du RBb.